Hello. How would I factor the following?

7(x-1)-x(x+1)

a^{2}-36

b^{2}+5b+6

Thank you!

Guest Mar 5, 2017

#1**+5 **

a^{2}-36

This is a standard difference of two squares so: a^{2} - 36 → a^{2} - 6^{2} → (a+6)(a-6)

b^{2}+5b+6 → (b + 2)(b + 3)

7(x-1)-x(x+1) doesn't factor nicely at all as far as I can see!

.

Alan
Mar 5, 2017

#2**0 **

For questions like

\(b^2+5b+6\)

you need to look for 2 numbers that multiply to be +6

Since it is + they both must be + or both -

BUT

they have to add to be +5 so they both must be +

ok

we have

1*6=6 but 1+6 is not 5

2*3=6 and 2+3=5 BINGO!

so we have

\(b^2+5b+6=(b+2)(b+3)\)

Just like Alan said :)))

Melody
Mar 5, 2017